Principals’ Use of Student Mentorship Programmes and Students’ Discipline in Secondary Schools in Machakos County, Kenya - Patrick M., Wambua; Jeremiah M., Kalai; Ursula, A, Okoth (European Scientific Journal, ESJ, 2017)
Studies have advocated for participatory governance in education (Kindiki, 2009, Tikoko& Kiprop, 2011). There is however a dearth of literature on use student mentoring in relation to discipline. The purpose of this study was investigating principals’ use of student mentorship programmes and students’ discipline in secondary schools in Machakos County, Kenya. The study sought to establish the focus of student mentoring and determine significant relationships existed between principals’ use of successful alumni, mentoring on ethical living and students’ discipline in secondary schools. The study used systems theory by Ludwig Bartalanffy which postulates that schools are part of the environment in which they operate and influence and get influenced by other systems. Questionnaires for principals and student leaders were used. Cross-sectional survey design was adopted with a target population of 354 secondary schools principals and 4602 student leaders. Probability sampling was employed and stratified proportionate random sampling was used. A sample of 118 secondary school principals and 1534 student leaders were sampled and the return rate consisted of 101(85.6%) principals, 100 teachers (100%) and 1433(93.4%) student leaders. Frequencies, percentages and Means were used to compare various forms of mentoring while correlation coefficients were used to determine the strengths of the association between the various participatory practices and establish if statistically significant or not. Student mentoring was practised in 66.3 per cent of schools with attendant reduced cases of indiscipline. There was a strong correlation between use of successful alumni, mentoring on academic excellence, mentoring on ethical living and student discipline.